THE ACCOUNTING EXCHANGE. (The Accounting Review, 1932)
For problems involving the admission of a new partner to a firm, when the books of the old firm are to be continued, two methods are suggested by different textbooks. Often the two accounting exchange methods are offered as alternatives. These two methods have been illustrated in the article. It can readily be seen that each of these solutions give effect to the conditions of the problem. The discussion makes it evident that the two solutions offered to the problem are not, in a true sense, alternatives. The selection of one of the two methods cannot safely be left to the whim of the accountant who drafts the entries. The principals, who do not at the time en- joy a community of interest, should be consulted and due consideration should be given to their respective equities. As a general rule it seems that there is more reason for setting up goodwill when the new partner is admitted rather than to credit the old partners with a bonus of a part of the new partner's investment. It is true that goodwill which had not been purchased by the firm would be set up on the firm's books.